HUBUNGAN KETERAMPILAN KOMUNIKASI INTERPERSONAL DAN KEPERCAYAAN DIRI SISWA KELAS X SMAN 1 GARUM KABUPATEN BLITAR - Utomo, Dinar Permadi; Harmiyanto, Harmiyanto (Jurnal Kajian Bimbingan dan Konseling, 2016)
This study uses descriptive correlational study in order to describe and to know whether or not interpersonal communication skills affect students’ self-confidence. The subject of the study includes the whole students of 10th grade at SMAN 1 Garum in the 2015/2016 academic year. The data analysis used in this study is descriptive analysis technique and Pearson product moment correlation. The result of the study shows that most of 10th grade students at SMAN 1 Garum of Blitar Regency have high level of interpersonal communication skills. In terms self-confidence, it is found that most of 10th grade students of SMAN 1 Garum of Blitar Regency also pose high level. The study suggests that there is significant correlation between interpersonal communication skills and self-confidence of 10th grade students at SMAN 1 Blitar of Blitar Regency. The result of the study shows that students with high level of communication skills also pose high level of self-confidence.